The Fiction of Agelessness:: Work, Leisure, and Aging in Alice Munro’s “Pictures of the Ice” - Jamieson, Sara (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2004)
In contrast to a contemporary ideal of positive aging that positions the elderly as self-reliant consumers of leisure, Alice Munro's representation of old age introduces realities such as relative poverty, dependence, and physical decline that place this ideal beyond the reach of many retired people. "Pictures of the Ice" portrays photographs, mirrors, and acts of seeing to acknowledge and critique the influence of visual impressions over perceptions of the old in our image-obsessed culture. Although Munro's protagonist, Austin Cobbett, does not literally appear in the titular "pictures," his presence therein is sensed by those he leaves behind, who cannot perceive him in any but visual terms.